Differential biochemical responses of seven Indian wheat genotypes to temperature stress - Satbhai Ravindra; Bharad Swati; Moharil Mangesh (BMC Plant Biology)
Abstract Background Changes in the temperature induction response are potential tools for the empirical assessment of plant cell tolerance. This technique is used to identify thermotolerant lines in field crops. In the present investigation, ten-day-old seedlings of six wheat genotypes released by Dr. PDKV, Akola, Maharashtra, India were exposed to gradual increases in high temperature and duration (control 25 °C to 30 °C for 1 h, 34 °C for 1 h, 38 °C for 2 h and 42 °C for 3 h) to investigate their effects on some physiological and biochemical parameters to provide basic information for improving heat-tolerant cultivars. Results Proline levels increased with increasing temperature up to 34 °C for 1 h but then decreased at higher temperatures (depending on genotype). Notably, proline levels decreased at 38 °C for 2 h in PDKV-Washim, AKAW-3722, and PDKV Sardar and at 42 °C for 3 h in all the genotypes. The relative leaf water content (RLWC) and chlorophyll 'b' content significantly decreased with increasing temperature. Hydrogen peroxide (H₂O₂) levels increased with temperature. The enzyme activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), and peroxidase also increased with temperature. However, these parameters, along with other biochemical indicators, generally decreased at 42 °C for 3 h. Conclusion This study revealed positive relationships between increasing temperatures. Hydrogen peroxide levels and the activities of SOD, APX, and peroxidase enzymes across all the genotypes. The AKAW-4627 genotype presented better maintenance of physiological and biochemical parameters and lower H₂O₂ levels, indicating greater heat tolerance. Compared with PDKV-Washim and AKAW-3722, which are more susceptible to high temperatures, the WSM-109–04, AKAW-4627 and PDKV Sardar genotypes presented better adaptability to heat stress. These findings suggest that selecting wheat genotypes with higher proline accumulation and better maintenance of physiological and biochemical parameters under heat stress, such as AKAW-4627, can help in the development of heat-tolerant wheat cultivars.